Relative Contribution of Odour Intensity and Valence to Moral Decisions. (March 2017) - Cecchetto, Cinzia; Rumiati, Raffaella Ida; Parma, Valentina
Meta-analytic evidence showed that the chemical senses affect moral decisions. However, how odours impact on morality is currently unclear. Through a set of three studies, we assess whether and how odour intensity biases moral choices (Study 1a), its psychophysiological responses (Study 1b), as well as the behavioural and psychophysiological effects of odour valence on moral choices (Study 2). Study 1a suggests that the presence of an odour plays a role in shaping moral choice. Study 1b reveals that of two iso-pleasant versions of the same neutral odour, only the one presented sub-threshold (vs. supra-threshold) favours deontological moral choices, those based on the principle of not harming others even when such harm provides benefits. As expected, this odour intensity effect is tracked by skin conductance responses, whereas no difference in cardiac activity – proxy for the valence dimension – is revealed. Study 2 suggests that the same neutral odour presented sub-threshold increases deontological choices even when compared to iso-intense ambiguous odour, perceived as pleasant or unpleasant by half of the participants, respectively. Skin conductance responses, as expected, track odour pleasantness, but cardiac activity fails to do so. Results are discussed in the context of mechanisms alternative to disgust induction underlying moral choices.